Behaviour of steel structures in seismic areas : selected, peer reviewed papers from the 9th International Conference on the Behavior of Steel Structures in Seismic Areas (STESSA 2018), February 14-17, 2018, Christchurch, New Zealand - Mazzolani, Federico M.; MacRae, Gregory A.; Clifton, George Charles, 1955- (Key engineering materials ;, 2018)
This collection of papers and keynote lectures presented at the 9th International Conference on the Behaviour of Steel Structures in Seismic Areas (Stessa2018, Christchurch, New Zealand, February 14-17, 2018) is a comprehensive overview of the recent state-of-the-art developments in the field of seismic resistant steel structures. The book is a valuable source for all stakeholders involving scientists, professionals, companies, and authorities dealing with the reduction of the seismic risk in earthquake prone countries.